PUTUSAN PENGADILAN TENTANG PENYALAHGUNAAN WEWENANG DALAM TINDAK PIDANA KORUPSI - Nur Basuki Minarno (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
From this research, it is found out that firstly the concept of power belongs to the regime of Administrative Law To prove the element of misuse of power therefore, it is necessary apply legal concept under Administrative Law regime. In practice, however to determine whether there is an element of misuse of power court relies upon principle of reasonableness and carefulness as a parameter that are only suitable to determine materially unlawful act. Doing as such, the court mixes up two parameters of different legal regimes in determining the element of misuse of power What court does is obviously incorrect because misuse of power is always intentionally carried out. Power is given due to certain purpose. lf the power is exerted for other than its purpose, this may be deemed as misuse of power Such principle is called principle of speciality Law given power is specified bylaw On the other hand, discretionary power is general principles of good administration based on the purpose.